Britain's gulag : the brutal end of empire in Kenya - Elkins, Caroline (London : Pimlico, 2005)
Caroline Elkins recounts the waning days of British Empire in Kenya, and the little known destruction of thousands of Kenyans at the hands of the British.
Originally published: London: Jonathan Cape.
Includes bibliographical references and index.
Winner of the 2006 Pulitzer prize for general non-fiction.
Keywords: History 1952-1960.; 1900-1999; Detention of persons -- Kenya -- History -- 20th century; Concentration camps; Detention of persons; Kikuyu; Mau-Mau.; Mau-Mau.; Kenya -- History -- Mau Mau Emergency, 1952-1960.; Kenya -- History -- Mau Mau Emergency, 1952-1960 -- Concentration camps; Kenya; Kikuyu; History